Scrotoschisis: Review in clinical and embryological perspective of a rare anomaly - Fikri, Erjan; Alnaz, Ahmad Razi Maulana; Abdillah, Aqyl Hanif; Az-Zahra, Salsabila (Journal of Neonatal Surgery, 2024)
Scrotoschisis is a rare congenital anomaly affecting the scrotum and testes, characterized clinically by a defect in the scrotal wall and extrusion of testicular tissue. This literature review is based on reports gathered from PubMed, Science Direct, and Google Scholar using relevant keywords to explore the underlying basic science of this rare condition. The etiology and mechanism of scrotoschisis development remain largely unknown, with only theoretical explanations and a lack of empirical evidence regarding its pathogenesis, which is thought to be linked to embryological abnormalities during scrotal formation. Diagnosing scrotoschisis typically involves a straightforward visual examination of the extruded testes immediately after birth, although clinical presentations may vary, being either unilateral or bilateral. Surgical intervention, primarily through orchidopexy, is generally beneficial for repositioning the testes, closing defects, and preventing potential complications. The prognosis for individuals with this anomaly is generally favorable, although long-term testicular function has been inadequately documented. Further research, including additional clinical reports and investigations involving animal models or embryological studies, is warranted to enhance our understanding of this condition.